Kinetics and mechanism of the interaction of pyridoxal hydrochloride and glucose with aromatic amines (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The kinetics and mechanism of the interaction of anesthetizin with pyridoxal hydrochloride and glucose were studied under comparable conditions. The condensation of anesthetizin with pyridoxal and glucose proceeds through two kinetically distinct stages: the first fast stage is the addition of the amine to pyridoxal and glucose to form amino alcohols; the second, slower stage is the dehydration of amino alcohols to form Schiff bases and N-glycosylamines. Schemes for the interaction of the condensation products of pyridoxal hydrochloride and glucose with anesthetizin are proposed.
Keywords: Vitamin B6, anesthetizin, Schiff bases, N-glycosylamine, glucose, condensation